Sociality of Future Teaching Staff and Solidarity of Society in the Context of Integration of New Subjects of Russia: Methodological Reflection - Ekaterina I. Stepanyuk (Peoples' Friendship University of Russia (RUDN University), 2024)
The problems of preserving social culture and ensuring social unity in the context of the special military operation and the integration of the Donetsk People's Republic, the Lugansk People's Republic, the Zaporizhzhia and Kherson Regions are of the utmost importance for the entire Russian society and the education system, including higher education. To solve them, it is necessary to provide methodological and humanitarian support for the process of studying and forming the sociality of the individual in new socio-cultural conditions. The purpose of this work is to methodologically substantiate the conceptual lines of forming the sociality of future teaching staff in the context of integration into the all-Russian educational space of new subjects of the Russian Federation. Based on reflection on the results of the complementary use of anthropological, axiological and praxeological approaches, as well as methodological procedures, the cognitive image of sociality was identified as having its essential features (as an integrative category) and conceptual development lines in culture and in the process of training future teaching staff (humanitarianism, psychological continuum of sociality, cultural identity and fundamental social constants, and some others). The interpretation of the essence of sociality as the personal ability to comprehend ideological, social and psychological knowledge and experience, to carry out responsible, innovative organization of social life in reasonable combination with individual interests, as well as the explication of significant characteristics expanded the traditional conceptual foundation of theories, principles, priorities and ideals of the movement towards social unity of people, towards the implementation of social activities of students in the context of integration into the all-Russian educational space. Through critical "selection" of strategies and technologies for the formation of sociality in future teaching staff, the "horizontality" of the value-semantic and humanitarian components of universal human culture has been supplemented, and their new understanding has been given in the context of the formation of traditional spiritual and moral values. The results of the study will form the basis for formatting educational programs and expert diagnostics, research projects, cultural, social and educational practices in universities of the new subjects of the Russian Federation, and can also be used in the process of studying the course "Fundamentals of Russian Statehood". Further research should be directed towards finding constructive technologies for the psychological and pedagogical deployment of sociality in a new socio-cultural space that will bring future teaching staff as close as possible to practical reality in the context of the integration of new subjects into the educational space of Russia.